Efficacy of repetitive transcranial magnetic stimulation in the prevention of relapse of depression: study protocol for a randomized controlled trial - Wang, Huaning (BioMed Central, 2013)
BACKGROUND: Depression is a chronic illness that generally requires lifelong therapy. Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive technique with few side effects that has been reported to be useful in the treatment of depression. However, no studies to date have evaluated in a randomized controlled trial (RCT) the efficacy of rTMS for maintenance treatment of depression. METHODS/DESIGN: In this article, we report the design and protocol of a randomized, single-blind, placebo-controlled, parallel-group, multicenter study in China to evaluate the efficacy of rTMS in the prevention of relapse of depressive symptoms. In total, 540 patients, aged 18 to 60 years, diagnosed with depression and experiencing an acute exacerbation of depressive symptoms, will be enrolled. The study will consist of four phases: a screening/tolerability phase of up to 7 days; an open-label, flexible-dose lead-in phase of 8 weeks; an open-label, fixed-dose stabilization phase of 6 weeks; and a single-blind relapse prevention phase of 12 months. During the open-label phase, all patients will be treated with venlafaxine. Remitters with Hamilton Rating Scale for Depression (HAM-D(17)) score ≤7 will be eligible to enter the single-blind phase and will be randomly assigned to one of three groups: group 1 on active rTMS and venlafaxine; group 2 on sham rTMS and venlafaxine; and group 3 on venlafaxine alone. Efficacy will be evaluated during the study using relapse assessment (time between subject randomization to treatment and the first occurrence of relapse). Secondary outcome measures will include: symptom changes, measured by the HAM-D(17); illness severity changes, measured by the Clinical Global Impression of Severity for Depression (CGI-S-DEP); and changes in subject functioning, assessed with the Personal and Social Performance (PSP)scale. Safety will be assessed throughout the study by monitoring of adverse events, clinical laboratory tests, electrocardiography (ECG), and measurements of vital signs (temperature, pulse, and blood pressure) and weight. Suicidality will be assessed by the Columbia Suicide Severity Rating Scale (C-SSRS). DISCUSSION: The result of this trial will assess the efficacy of rTMS in the prevention of relapse of symptoms of depression by determining whether rTMS in combination with an antidepressant is more efficacious than the antidepressant alone for maintenance of the clinical response. TRIAL REGISTRATION: ClinicalTrials.gov, NCT01516931